Modeling of Dynamic/Situational Leadership for Effective Entrepreneurship Development - Shaikh Sadique; Rafik Shaikh Shaikh (Journal of Model Based Research, 2019)
In this article we try to pay attention of readers, researchers and management executives how one can adapting situational leadership in another words dynamic leadership and enhance organization performance for goal attainment with high motivational leverages for effective team building and teamwork. We developed two models and explained how we should have to improve leadership qualities to lead business efficiently.
Keywords: team building